2020
DOI: 10.3390/app10175798
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in High-Alert Medication Treatment: A Study on the Cardiovascular Drug

Abstract: The safety of high-alert medication treatment is still a challenge all over the world. Approximately one-half of adverse drug events (ADEs) are related to high-alert medications, which motivates us to improve the predicament faced in clinical practice. The purpose of this study is to use machine-learning techniques to predict the risk of high-alert medication treatment. Taking the cardiovascular drug digoxin as an example, we collected the records of 513 patients who received the pertinent therapy during hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This study found that ML techniques can improve prediction accuracy for high alert drug (HAD) medication treatment, lowering the risk of ADEs, and improving medication safety. 61 Wongyikul et al created a HAD screening protocol with a ML model that used Gradient Boosting Classifier and screening parameters to identify HAD prescription errors from outpatient and inpatient drug prescriptions. The ML algorithm identified over 98% of actual HAD mismatches in the test set and 99% in the evaluation set when screening drug prescription events with a risk of HAD inappropriate use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that ML techniques can improve prediction accuracy for high alert drug (HAD) medication treatment, lowering the risk of ADEs, and improving medication safety. 61 Wongyikul et al created a HAD screening protocol with a ML model that used Gradient Boosting Classifier and screening parameters to identify HAD prescription errors from outpatient and inpatient drug prescriptions. The ML algorithm identified over 98% of actual HAD mismatches in the test set and 99% in the evaluation set when screening drug prescription events with a risk of HAD inappropriate use.…”
Section: Resultsmentioning
confidence: 99%
“…The risk warning platform was developed to predict PIP, PIM, and PPO, with acceptable accuracy, prediction performance, and clinical application potential. Tai, C.-T, 2020 61 Taiwan To predict the risk of high-alert medication treatment (digoxin) using machine-learning techniques Retrospective analysis This study included patients who had accepted digoxin therapy while hospitalized between January 2004 and December 2013. AUC values ranged from 0.551 to 0.836.…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicated articles, 3,346 studies were screened by the title and/or abstract, 3,175 irrelevant studies were excluded and 171 articles were included for full‐text review. Finally, 64 articles related to precision dosing using ML were included for analysis 11–74 . The PRISMA flow diagram representing the study selection process and review results is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Previous machine learning studies used several variables including drug-to-drug interaction, demographic items, laboratory items, and medical history to set up optimal SDC prediction models with the AUC ranging from 0.533 to 0.912 [ 29 , 30 ]. Importantly, our deep learning model predicted high-risk digoxin toxicity patients by ECG only with the AUC of 0.912.…”
Section: Discussionmentioning
confidence: 99%